2004
DOI: 10.1007/s00234-004-1246-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between high-grade gliomas and solitary metastases using peritumoral 3-T magnetic resonance spectroscopy, diffusion, and perfusion imagings

Abstract: This study compared the effectiveness of relative cerebral blood volume, apparent diffusion coefficient, and spectroscopic imaging in differentiating between primary high-grade gliomas and solitary metastases. A 3.0-T MR unit was used to perform proton MR spectroscopy, diffusion imaging, and conventional MR imaging on 26 patients who had solitary brain tumors (14 high-grade gliomas and 12 metastases). All diagnoses were confirmed by biopsy. Twelve perfusion MR studies (8 high-grade gliomas and 4 metastases) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
151
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(187 citation statements)
references
References 22 publications
24
151
2
6
Order By: Relevance
“…Small studies have suggested that other tests such as dynamic contrast-enhanced MRI, perfusion imaging, and magnetic resonance spectroscopy may help differentiate between brain metastases and high-grade gliomas. 15,16 The bulk of the literature regarding the use of brain CT or MRI for staging purposes has dealt with lung cancer. Nevertheless, there is still no general agreement on when to use CT or MRI as part of the initial staging evaluation for a patient newly diagnosed with lung cancer.…”
Section: Ct/mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies have suggested that other tests such as dynamic contrast-enhanced MRI, perfusion imaging, and magnetic resonance spectroscopy may help differentiate between brain metastases and high-grade gliomas. 15,16 The bulk of the literature regarding the use of brain CT or MRI for staging purposes has dealt with lung cancer. Nevertheless, there is still no general agreement on when to use CT or MRI as part of the initial staging evaluation for a patient newly diagnosed with lung cancer.…”
Section: Ct/mrimentioning
confidence: 99%
“…25 However, new MRI methods (perfusion and magnetic resonance spectroscopy) have shown improvement in specificity. 15,16 Identification of a solitary brain lesion in a patient with a controlled extracranial primary cancer with no other sites of disease on systemic evaluation should be followed by MRI with increased dose of contrast and, if no additional lesions are identified, histologic verification. In patients found to have multiple brain lesions with imaging characteristics compatible with metastases, the decision whether to pursue histologic confirmation is based on the clinical picture.…”
Section: Pathologic Confirmationmentioning
confidence: 99%
“…For instance, a recent study of 51 patients with metastatic brain lesions found that 18 lesions were hypointense on diffusion-weighted sequences, 17 were hyperintense and 16 were isointense [63]. However, several studies have suggested that ADC values may be useful to distinguish solitary metastases from primary brain malignancies [64][65][66]. Specifically, although peritumoral oedema is common in both metastases and primary brain malignancies, the ADC values in the peritumoral oedema of metastases have been shown to be higher than those of primary brain malignancies.…”
Section: Neoplastic Malignant Metastasesmentioning
confidence: 99%
“…In recent years, there has been a shift towards advanced MRI techniques, such as magnetic resonance spectroscopy ( 1 H-MRS), diffusion weighted imaging (DWI), diffusion tensor imaging (DTI) and perfusion weighted imaging (PWI), in order to resolve demanding diagnostic problems. These techniques offer a more detailed and non-invasive evaluation of brain tumors [1][2][3] and have added incremental diagnostic information regarding brain tumor characterization over conventional MRI alone [4,5] . 1 H-MRS has been studied for more than a decade as a promising diagnostic tool for a variety of pathologies.…”
Section: Introductionmentioning
confidence: 99%